2021
DOI: 10.1186/s13071-021-04946-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of tick-borne pathogens in questing Ixodes ricinus ticks from Wester Ross, Northwest Scotland

Abstract: Background Lyme borreliosis and other tick-borne diseases emerge from increased interactions between humans, other animals, and infected ticks. The risk of acquiring a tick-borne infection varies across space and time, so knowledge of the occurrence and prevalence of pathogens in ticks can facilitate disease diagnosis in a specific area and the implementation of mitigation measures and awareness campaigns. Here we identify the occurrence and prevalence of several pathogens in Ixodes ricinus tic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Another recently published study, still on questing ticks, revealed a 4.7% prevalence of A. phagocytophilum in Wester Ross, the northwest area of the Scottish Highlands, with A. phagocytophilum being the most prevalent tick-borne pathogen detected. According to the authors, the majority of the strains (86%) were identified as the zoonotic ecotype I, probably maintained by red deer, and the remaining (14%) as the non-zoonotic ecotype II, probably maintained by roe deer [ 23 ]. An eco-epidemiological screening of the rodent community in West Wales revealed a low prevalence of A. phagocytophilum, which was detected only at one site in ticks collected from bank voles [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another recently published study, still on questing ticks, revealed a 4.7% prevalence of A. phagocytophilum in Wester Ross, the northwest area of the Scottish Highlands, with A. phagocytophilum being the most prevalent tick-borne pathogen detected. According to the authors, the majority of the strains (86%) were identified as the zoonotic ecotype I, probably maintained by red deer, and the remaining (14%) as the non-zoonotic ecotype II, probably maintained by roe deer [ 23 ]. An eco-epidemiological screening of the rodent community in West Wales revealed a low prevalence of A. phagocytophilum, which was detected only at one site in ticks collected from bank voles [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ixodes ricinus also transmits Ca. Neoehrlichia mikurensis, which has been found all across Europe except for the United Kingdom [6][7][8]. The number of studies describing human infections involving Ca.…”
Section: Introductionmentioning
confidence: 99%
“…Lyme disease causing spirochetal bacteria belonging to Borrelia burgdorferi sensu lato are also transmitted to different hosts by ticks (Stewart and Bloom, 2020). Increasing rate of co-infections by these two pathogens have been reported in the endemic regions of the United States (Swanson et al, 2006;Diuk-Wasser et al, 2016;Wormser et al, 2019) and Europe (Olsthoorn et al, 2021). Thus, in addition to B. burgdorferi-Babesia co-infections, simultaneous Babesia-Anaplasma phagocytophilum infections are also reported because tick vector and white footed mouse, Peromyscus leucopus (and other reservoir hosts) harbor several pathogens together.…”
Section: The Epidemiology Of Protozoa-bacteria Co-infectionsmentioning
confidence: 99%